Carnations and the floriculture industry: documenting the cultivation and marketing of flowers in Colorado - Liu, Shu, author; Meyer, Linda M., author; The Haworth Press, Inc., publisher (Colorado State University. Libraries, 2008)
The Records of the Colorado Flower Growers Association (CFGA) is an archival collection documenting the association prior to its 1979 name change. The CFGA was founded in 1928 to support the production and marketing of greenhouse flowers grown commercially in the state. In 1979, the organization changed its name to the Colorado Greenhouse Growers Association to reflect the increasing diversification of the industry. The collection consists of documents dated 1928 to 1980 (with the bulk falling between 1958 and 1972), and includes minutes from general, board and committee meetings, correspondence, newsletters, financial reports, scrapbooks, clippings, and photographic materials. This article provides a history of Colorado carnations, information on the collection, and describes a digital project supported by a cooperative agreement between the Agriculture Network Information Center (AgNIC) and the Colorado State University (CSU) Libraries to make a selection of the scrapbooks, clippings, newsletters, and photographic materials available online to researchers through the AgNIC Web site. In addition to providing access to over 500 digital images, project staff developed important metadata to facilitate their discovery, retrieval, and management using the Standard NAL Metadata and the Collaborative Digitization Project (CDP)'s CDP Dublin Core Metadata Best Practices.
Final, peer-reviewed manuscript.
Keywords: Colorado Flower Growers Association; floriculture industry; flowers; Colorado; carnations; CFGA; digital collection; digital project